Gaining Business Advantage From Climate Change - Demetriadi, Marilena (2005)
Over the last decade there has been much debate over the impact of climate change. The water industry in England and Wales could be significantly impacted, radically altering the availability of its natural resources and testing the resilience of the present infrastructure. This is likely to result in the provision of water and wastewater services to customers in the future becoming ever more challenging. It is likely that this will require a shift in business strategy to react or take advantage of the effects of climate change. Some form of intervention is necessary but climate change could also provide new offerings catapulting the organisation into diverse profitable ventures.